The effect of dietary hydroxyproline and dietary oxalate on urinary oxalate excretion in cats. Issue 2 (1st February 2014) - Dijcker, J. C.; Hagen-Plantinga, E. A.; Thomas, D. G.; Queau, Y.; Biourge, V.; Hendriks, W. H.
Abstract: In humans and rodents, dietary hydroxyproline (hyp) and oxalate intake affect urinary oxalate (Uox) excretion. Whether Uox excretion occurs in cats was tested by feeding diets containing low oxalate (13 mg/100 g DM) with high (Hhyp-Lox), moderate (Mhyp-Lox), and low hyp (Lhyp-Lox) concentrations (3.8, 2.0, and 0.2 g/100 g DM, respectively) and low hyp with high oxalate (93 mg/100 g DM; Lhyp-Hox) to 8 adult female cats in a 48-d study using a Latin square design. Cats were randomly allocated to one of the four 12-d treatment periods and fed according to individual energy needs. Feces and urine were collected quantitatively using modified litter boxes during the final 5 d of each period. Feces were analyzed for oxalate and Ca, and urine was analyzed for specific density, pH, oxalate, Ca, P, Mg, Na, K, ammonia, citrate, urate, sulfate, and creatinine. Increasing hyp intake (0.2, 2.0, and 3.8 g/100 g DM) resulted in increased Uox excretion (Lhyp-Lox vs. Mhyp-Lox vs. Hhyp-Lox; P < 0.05), and the linear dose-response equation was Uox (mg/d) = 5.62 + 2.10 × g hyp intake/d ( r 2 = 0.56; P < 0.001). Increasing oxalate intake from 13 to 93 mg/100 g DM did not affect Uox excretion but resulted in an increase in fecal oxalate output ( P < 0.001) and positive oxalate balance (32.20 ± 2.06 mg/d). The results indicate that the intestinal absorption of the supplemental oxalate, and thereby its contribution to Uox, was low (5.90% ± 5.24%). Relevant increases in endogenous Uox excretion were achieved by increasing dietary hyp intake. The hyp-containing protein sources should be minimized in Ca oxalate urolith preventative diets until their effect on Uox excretion is tested. The oxalate content (up to 93 mg/100 g DM) in a diet with moderate Ca content does not contribute to Uox content.